Resistance as negotiation: making states and tribes in the margins of modern India - Chandra, Uday (Ranikhet Cannt Permanent black and ashoka university, 2024)
(3z(BTribes(3y (Bappear worldwide today as vestiges of a pre-modern past at odds with the workings of modern states. Acts of resistance and rebellion by groups designated as (3z(Btribal(3y (Bhave fascinated as well as perplexed administrators and scholars in South Asia and beyond. Tribal resistance and rebellion are held to be tragic yet heroic political acts by (3z(Bsubaltern(3y (Bgroups confronting omnipotent states. By contrast, this book draws on fifteen years of archival and ethnographic research to argue that statemaking is intertwined inextricably with the politics of tribal resistance in the margins of modern India.s
Keywords: Asian Studies; Anthropology; Comparative Politics